What Really Ails the Eurozone?: Faulty Supranational Architecture - Assaf Razin; Steven Rosenfielde (Contemporary Economics, 2012)
The global financial crisis which erupted in the United States instantaneously swept across Europe. Like the United States, the European Monetary Union (EMU) was ripe for a crash. It had its own real estate bubble, specifically in Ireland and Spain, indulged in excessive deficit spending, financially deregulated, and rapidly expanded credit. Policy responses and recovery patterns for key EU members like Germany, France (within the Eurozone) and the United Kingdom (outside the Eurozone) were similar. However, after the bubble burst and the crisis began unfolding it became clear that the Eurozone plight differed from America's in one fundamental respect. There was no exact counterpart of Eurozone GIIPS (Greece, Italy, Ireland, Portugal and Spain) in the United States. The disparity is traced to the EU's and Eurozone's special form of governance called 'supranationality' (a partially sovereign transnational organization) that has been largely ignored in economic treatises about the costs and benefits of customs unions, economic communities, and monetary unions. EZ members have put themselves in a monetary cage, akin to the gold standard. Member states have surrendered control over their monetary and foreign exchange rate policies to the German dominated European Central Bank (ECB), without supplementary central fiscal, private banking and political union institutions. This should be enough in general competitive theory, but too often leads to factional and societal gridlock that compounds the misery, and could cause the EU to permanently and gravely underperform relative to community's 'un-caged' potential.
Keywords: E0; F0; F02; F5; F30; 330; single currency area; supranationality; EU; EMU